Breeding strategy to improve Ethiopian Boran cattle for meat and milk production - Haile, Aynalem; Workneh, A.; Tegegne, Azage; Kebede, N.; Dessie, Tadelle (International Livestock Research Institute, 2011)
In Ethiopia, genetic improvement of the indigenous cattle for dairy production, focusing on crossbreeding, has been practised for the last five decades, albeit with little success. Selection as an improvement tool has been given less emphasis and as such there have been no systematic and organized selection schemes for cattle genetic improvement in Ethiopia. In addition, little or no genetic improvement work targeted at improving beef production has been undertaken so far. Therefore, there is a need to develop effective and sustainable genetic improvement schemes for indigenous cattle breeds of Ethiopia. This report is prepared to develop breeding plans for the Ethiopian Boran cattle and is based on: 1) secondary data sources that include literature review from earlier works on Ethiopian Boran cattle; 2) results of data collected and analysed from dairy herds at Debre Zeit research Station of the International Livestock Research Institute (ILRI) and the Holetta Agricultural Research Center of the Ethiopian Institute of Agricultural Research (EIAR); 3) detailed desk work to design the improvement program; and 4) suitability analysis for Boran cattle using GIS. Ethiopian Boran, although a beef breed in many tropical countries, has been used as a dairy animal in many development and experimental activities in Ethiopia. The breed has been found to be fast growing, fertile and good milk producer compared to other indigenous cattle breeds in Ethiopia. The growth, reproduction and milk production performance of Boran has been improved in different parts of the world including Kenya, South Africa, Australia and USA. This indicates the huge potential of the breed that could be tapped if appropriate breeding strategy supported by proper management could be designed and fully implemented. In this report, selection scheme based on open nucleus breeding program is suggested to improve the beef and dairy attributes of the Ethiopian Boran cattle. Where crossbreeding is an option to improve dairy performance, a detail operational scheme is also suggested. Suitability of Ethiopian Boran cattle to different locations in Ethiopia is also mapped using GIS.